The collision of tradition and modernity: interpreting the cultural characteristics of chinese animated public service announcements - Li, YiXuan; Harun, Azahar; Rao, DongYu (Universiti Teknologi MARA, Kedah, 2025)
The contemporary presentation and interpretation of traditional culture is an issue that requires continuous exploration and practice. This paper explores the mingling and collision of tradition and modernity in Chinese animated Public Service Announcements (PSAs), as well as the relationship between traditional culture’s values and the problems modern society faces. This study employs the expression of traditional Chinese elements in contemporary animated PSAs through content analysis, focusing on animation’s unique communicative features and contemporary relevance. These advertisements break the traditional propaganda mode to a certain extent, revealing the inheritance, transformation, and reproduction of traditional culture in modern society. Therefore, this paper explores both the presentation and cultural characteristics of traditional Chinese elements in contemporary animated PSAs, fights against cultural impact and expresses cultural confidence through disseminating traditional values, and finally summarises the use of visual style, storyline, and sound effects in animated PSAs.